Firm capabilities and export performance of small firms: A meta-analytical review. Issue 5 (October 2021) - Gupta, Parul; Chauhan, Sumedha
Abstract: Despite its importance, there is no clear understanding of the impact of small firms' capabilities (networking, innovation, and marketing) on their export performance. This article attempts to address this issue with a meta-analysis of 74 recent empirical studies comprising 76 independent samples and covering more than 30 countries. We found that innovation, marketing, and networking capabilities positively influence export performance of small firms. However, the context-dependent nature of these relationships demands a more fine-grained examination. The variations in the ES of these relationships are explained by the role of external business environmental factors prevailing in the country of origin of the firm (developing/developed country and individualism/collectivism culture). We examined the divergent results provided by empirical studies using the moderator analysis. The findings of this article shed light on the role of small firms' capabilities in enhancing export performance in different contextual settings.